Penerapan Kaizen dan CRM dalam Meningkatkan Daya Saing UMKM Bulu Mata di Purbalingga - Telma Anis Safitri; Isti Riana Dewi; Asmi Ayuning Hidayah; Dwi Astarani Aslindar (Sinergi Abdimas Jurnal Pengabdian Masyarakat, 2025)
Eyelash SMEs in Purbalingga have great potential to grow, but still face challenges such as disorganized workplaces, low operational efficiency, and a lack of effective customer relationship management. This community engagement program aims to enhance the competitiveness of these SMEs through the application of Kaizen principles using the 5S method, as well as Customer Relationship Management (CRM) strategies. The implementation involved problem identification, training, execution, monitoring, and evaluation. The results show significant improvements in productivity, product quality, and customer satisfaction and loyalty. The application of Kaizen created a more efficient and organized work environment, while CRM strengthened customer relationships through a more personal and structured approach. This program demonstrates that the synergy between operational improvement and relational marketing strategies can be an effective solution to increase the competitiveness of SMEs in an increasingly competitive market.